Shared zones of optimal functioning: A framework to capture peak performance, momentum, psycho-bio-social synchrony, and leader-follower dynamics in teams - Filho, E. (Journal of Clinical Sport Psychology, 2020)
By bridging the literature on shared mental models and the individual zones of optimal functioning, the author advances a new framework called the shared zones of optimal functioning. The shared zones of optimal functioning is a probabilistic methodology designed to (a) capture optimal and suboptimal performance experiences in teams, (b) track team momentum through the analysis of within-team performance fluctuations, and (c) estimate within-team psycho-bio-social synchrony and leader-follower dynamics (i.e., leader-follower dichotomy, shared leadership). To test the shared zones of optimal functioning framework, three dyadic juggling teams were asked to juggle for 60 trials, while having their performance, arousal, pleasantness, and attentional levels recorded. Ordinal logistic regression, frequency counts, and cross-correlation analyses revealed that each team showed idiosyncratic affective and attentional levels linked to optimal performance, team momentum patterns, and leader-follower dynamics. The implications of these findings for the development of high-performing teams and specific avenues of future research are discussed throughout.